Making sense in the city: Dolly Parton, early reading and educational policy-making - Hall, Christine; Jones, Susan (Wiley, 2016)
In this paper, we present a case study of a philanthropic literacy initiative, Dolly Parton's Imagination Library, a book-gifting scheme for under 5s, and consider the impact of the scheme on literacy policy in the English city where it was introduced. We bring four lenses to bear on the case study. First, we analyse the operation of the scheme in the community it was intended to serve; second, we consider the case study as an early literacy intervention aimed at promoting reading development; then we consider it from the perspective of theories about marketing and branding; and finally, we analyse it from the perspective of new philanthropy theory. We use these lenses to help us make sense of the current pressures on educational policy-making in English cities, as city officials struggle to manage competing political agendas, to initiate reforms in situations where they have significant responsibilities but reduced power, and to maintain the distinctiveness of the places they represent. We argue for the need to reassess our understandings of the ways that literacy policies are made at the local level within this rapidly changing context.